POLİPİROLÜN POLİÜRETAN ESASLI KOMPOZİTLERİN ÖZELLİKLERİNE ETKİSİ - Yanilmaz, Meltem; Kalaoğlu, Fatma; Karakaş, Hale; Saraç, A. Sezai (Ege Üniversitesi, 2011)
In this study, the polyurethane based composites were prepared by solvent casting from dimethylformamid (DMF) solutions of Polyurethane-Polypyrrole (PU-PPy) in order to obtain the polyurethane based composites with enhanced dielectric properties for smart textile applications. From this research, it can be concluded that Glass Transition Temperature (Tg) values of the composites were influenced by the number of hydrogen bonds formed inside polyurethane in the presence of PPy. When the initial amount of pyrrole was increased, the Tg values of the composites were seen to increase. A correlation of the glass transition temperatures of the samples, determined by Differential Scanning Calorimeter (DSC) and Dynamic Mechanical Analyzer (DMA) via Young’s modulus, showed that the increase of PPy reduced mobility and increased the glass transition temperature and modulus. Dielectric study results indicated that ~20% wt. Pyrrole (Py) increases dielectric constant above 7000 and these composites can be good candidates for electrical application

Bu çalışmada, poliüretan-polipirol çözeltisinden dimetil formamid(DMF) çözücüsü kullanılarak tekstil uygulamaları için dielektrik özellikleri iyileştirilmiş poliüretan bazlı kompozitler elde edilmiştir. Bu çalışma ile polipirol varlığında kompozit malzemelerin camsı geçiş sıcaklığının (Tg), poliüretan içerisindeki hidrojen bağı miktarından etkilendiği sonucu çıkarılabilir. Pirolün başlangıç miktarı arttırıldığında, kompozit malzemelerin Tg değerlerinin arttığı görülmüştür. Diferansiyel Taramalı Kalorimetreden (DSC) elde edilen camsı geçiş sıcaklığı ve Dinamik Mekanik Analiz cihazından (DMA) elde edilen Young modülü sonuçlarının korelasyonu, polipirol arttıkça kompozitlerin hareket kabiliyetinin düştüğünü; camsı geçiş sıcaklığının ve modülünün arttığını göstermiştir. Dielektrik çalışmalarına göre, başlangıçta %20 Pirol içeren kompozit malzemenin dielektrik sabiti 7000’ in üzerindedir ve bu malzemeler elektriksel uygulamalar için iyi birer adaydır
Keywords: Poliüretan; Pirol; Camsı geçiş; Young modülü; FTIR-ATR; Polyurethane; Pyrrole; Glass transition; Young’s modulus; FTIR-ATR